Strategi Dinas Kesehatan Provinsi Jawa Tengah dalam Mengatasi Stunting - Amalia Mulyani; Fauzan Hidayatullah; Hasya Rahmah; Sugih Sugiharta; Ricardo Cordias; Noer Apptika Fujilestari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Stunting in children under five is a critical health problem that affects physical and cognitive development as well as potential future productivity. In Indonesia, the prevalence of stunting is still high, especially in Central Java. This research explores the Central Java Health Service's strategy in overcoming stunting through a qualitative approach using library research. This research shows the results that the Central Java Health Service has formulated policies in accordance with the RPJMN and the direction of the Ministry of Health, focusing on improving health status at all stages of life. Flagship programs such as